Pengaruh Siklus Pencelupan-Pengeringan Pada Pembuatan Film Tipis Tembaga Oksida Berbasis Nitrat Dengan Konsentrasi 0,4M Sebagai Solar Selektif Absorber - Septian, Handika; Amri, Amun; Herman, Syamsu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Solar Selective Absorber (SSA) is a thin film at the coating surface of the collector that absorbs solar radiation selectively and convert it into maximum heat energy. Solar selective absorber can be synthesized using sol-gel dip-coating method. The purpose of research is to synthesize the thin film of copper oxide solar selective absorber from copper nitrate precursor using sol-gel dip coating methode, to know the influence dipping-drying cycle variation to absorptance value. Pieces of aluminum with size 2x4x0.5cm were cleaned using a solution of phosphoric acid 10% at temperature 50oC for 10 minutes. Sol precursor was prepared by disolved copper nitrate trihidrate 0,4M and propio nic acid in ethanol. The sol prekursor was stirred for 2 hours at room temperature. The coating was synthesized by varying the number of dipping-drying cycles 1x, 2x, 3x, 4x, 6x, 8x and 10x, then annealed at temperature 550 ºC for 1 hour. Reflektance spectra in the area of UV-Vis-NIR show that increased cycles of dip-coating increase the value of absorptance (α). The results showed that the highest absorptance value found in coatings which was synthesized using copper oxyde 0.4M at 10x cycles with absorptance (α) = 74.32%.Keywords : dip-coating, energy, film, solar selective absorber, sol-gel